Obstructive Sleep Apnea, Oxidative Stress and Cardiovascular Disease: Lessons from Animal Studies - Dumitrascu, Rio (Hindawi Publishing Corporation, 2013)
Obstructive sleep apnea (OSA) is an independent risk factor for cardiovascular (CV) diseases such as arterial hypertension, heart failure, and stroke. Based on human research, sympathetic activation, inflammation, and oxidative stress are thought to play major roles in the pathophysiology of OSA-related CV diseases. Animal models of OSA have shown that endothelial dysfunction, vascular remodelling, and systemic and pulmonary arterial hypertension as well as heart failure can develop in response to chronic intermittent hypoxia (CIH). The available animal data are clearly in favour of oxidative stress playing a key role in the development of all of these CV manifestations of OSA. Presumably, the oxidative stress is due to an activation of NADPH oxidase and other free oxygen radicals producing enzymes within the CV system as evidenced by data from knockout mice and pharmacological interventions. It is hoped that animal models of OSA-related CV disease will continue to contribute to a deeper understanding of their underlying pathophysiology and will foster the way for the development of cardioprotective treatment options other than conventional CPAP therapy.